Transcriptional repression by PRC1 in the absence of H2A monoubiquitylation. - Pengelly, A.R.; Kalb, R.; Finkl, K.; Müller, J. (Genes & Development, 2015)
Histone H2A monoubiquitylation (H2Aub) is considered to be a key effector in transcriptional repression by Polycomb-repressive complex 1 (PRC1). We analyzed Drosophila with a point mutation in the PRC1 subunit Sce that abolishes its H2A ubiquitylase activity or with point mutations in the H2A and H2Av residues ubiquitylated by PRC1. H2Aub is essential for viability and required for efficient histone H3 Lys27 trimethylation by PRC2 early in embryogenesis. However, H2Aub-deficient animals fully maintain repression of PRC1 target genes and do not show phenotypes characteristic of Polycomb group mutants. PRC1 thus represses canonical target genes independently of H2Aub.